Combination Treatment of Splinting with Wire Composite and Artificial Tooth Pontic for Improved Aesthetics: A Case Report - Ersa, Savana; Amalia, Martina (Indonesian Journal of Case Reports, 2024)
Advanced bone loss in patients with periodontitis often leads to increased tooth mobility, sometimes resulting in tooth loss. The mobility of teeth necessitates splinting to optimize periodontal treatment outcomes in terms of aesthetics and periodontal health. This case report presents a novel approach using an artificial tooth pontic as a periodontal splint, utilizing wire stabilization to prevent severe tooth mobility and enhance esthetics. A 37-year-old male with aggressive periodontitis (Stage III, Grade C) exhibited extensive periodontal destruction, particularly in the upper and lower anterior regions. Pathological migration was evident following the loss of teeth 31 and 41, with additional anterior teeth in the lower jaw showing mobility and trauma from occlusion, notably tooth 33. The patient underwent nonsurgical periodontal therapy, including scaling, subgingival debridement, occlusal adjustment, and splinting. Stabilization was achieved by applying a wire splint from teeth 34 to 43, incorporating an artificial tooth pontic. Subsequent evaluations revealed improvements in clinical parameters such as probing pocket depth, tooth mobility, and bleeding on probing during supportive periodontal therapy visits. The splint remained stable, and the patient expressed satisfaction with their appearance remaining unaffected. This case demonstrates that severe tooth mobility can be effectively stabilized using a composite wire splint and an artificial tooth pontic, enhancing the patient's esthetic outcomes.